2017
DOI: 10.1155/2017/4042902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Laser Speckle Contrast Imaging for the Assessment of Oral Mucosal Blood Flow following Periodontal Plastic Surgery: An Exploratory Study

Abstract: The laser speckle contrast imaging (LSCI) is proved to be a reliable tool in flap monitoring in general surgery; however, it has not been evaluated in oral surgery yet. We applied the LSCI to compare the effect of a xenogeneic collagen matrix (Geistlich Mucograft®) to connective tissue grafts (CTG) on the microcirculation of the modified coronally advanced tunnel technique (MCAT) for gingival recession coverage. Gingival microcirculation and wound fluid were measured before and after surgery for six months at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
32
1
Order By: Relevance
“…This apico‐coronal direction was also confirmed in a series of case studies by Mormann (Mormann & Ciancio, ; Mormann, Meier, & Firestone, ), who found that marginal gingival perfusion is sensitive to the horizontal incision. This observation is in agreement with another cohort study in which, following tunnel preparation, more severe and longer ischemia was observed in the marginal area of the flap compared to its apical and proximal areas (Molnar et al, ). On the other hand, clinical observations revealed that the marginal gingiva could survive after horizontal incision and it could be revascularized by rapidly developing anastomosis from the periodontal plexus (Cutright, ; Kennedy, ).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…This apico‐coronal direction was also confirmed in a series of case studies by Mormann (Mormann & Ciancio, ; Mormann, Meier, & Firestone, ), who found that marginal gingival perfusion is sensitive to the horizontal incision. This observation is in agreement with another cohort study in which, following tunnel preparation, more severe and longer ischemia was observed in the marginal area of the flap compared to its apical and proximal areas (Molnar et al, ). On the other hand, clinical observations revealed that the marginal gingiva could survive after horizontal incision and it could be revascularized by rapidly developing anastomosis from the periodontal plexus (Cutright, ; Kennedy, ).…”
Section: Introductionsupporting
confidence: 92%
“…Prolonged ischemia at the apical side was counterbalanced by increased permeability of the vessels—indicated by higher wound fluid production—which facilitates the diffusion of nutritive compounds. The negative correlation between blood flow and wound fluid production has been observed previously in humans after periodontal plastic surgical procedures (Molnar et al, ) and in mice after skin grafting (Shaterian et al, ).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The laser speckle contrast imager (LSCI) is a more recent advancement in microvascular imaging, which proved to be useful in measuring the microcirculation of the human gingiva with high spatial and temporal resolution simultaneously . Taking the opportunity provided by the high spatial resolution, a new method was designed to study the remote effects of various drugs when applied to a small restricted area on the human gingiva.…”
Section: Introductionmentioning
confidence: 99%